ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS DALAM MENYELESAIKAN SOAL OPEN-ENDED PADA SISWA BERKEPRIBADIAN EKSTROVERT - Rahayu, Eko Sri; Wibowo, Teguh; Kurniawan, Heru (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
This study aims to analyze the mathematical creative thinking abilities of class VII extrovert students in solving open-ended questions on flat shape material. This type of research is qualitative research with a phenomenological approach. This study involved 3 seventh graders studnets who were taken using purposive sampling technique as research subjek. The instrument used for taking prospective subjects is the extrovert personality questionnaire. The data collection techniques used are tests of creative thinking abilities, interviews and field notes.  The data analysis techniques in this study used technical triangulation, namely data redduction, presentation data and conclusion. The results of the study show that extroverted students bring out aspects of novelty and flexibility. Based on research results, the creative thinking abilities of extroverted students is classified at level 2 (Quite Creative). Extrovert students need a discussion space to get feedback so they can issue or present their ideas fluently.